Microbiota of table olive fermentations and criteria of selection for their use as starters - Heperkan, Dilek (Frontiers in Microbiology, 2013)
Fermentation is one of the oldest methods for preserving of olives applied worldwide for thousands of years. However, olive processing is a speculative area where whether olives are fermented products or pickled products produced by organic acids and salt. Although lactobacilli and yeasts play a major role in the process, literature survey indicates that lactobacilli are less relevant at least in some types of natural green olives during fermentation. There have been significant advances recently in understanding the process to produce olives, especially the role of lactic acid bacteria (LAB) and yeasts including biofilm formation on olive surfaces by these organisms. The purpose of this paper is to review the latest developments regarding the microbiota of olives on the basis of olive types, their role on the fermentation process, the interaction between both group of microorganisms and the olive surface, the possibility to use starter cultures and the criteria to select appropriate cultures.